Obesity in Adults: Causes, Health Consequences, and Treatment Methods - Jakubiec, Joanna; Gmitrzuk, Julita; Malinka, Zuzanna; Wiśniewska, Katarzyna; Jachymek, Anna; Opatowska, Martyna; Kucharski, Tomasz; Karasiński, Maciej (Quality in Sport, 2024)
Introduction Obesity is defined as an excessive accumulation of body fat that can negatively affect a person’s physical as well as mental health. It results not only from excessive caloric intake relative to energy expenditure, but also from a myriad of genetic, metabolic, environmental and behavioral factors. Obesity poses the risk of a number of chronic diseases that impair quality of life and increase the risk of death. Understanding the causes of obesity, the consequences it brings, and learning about treatments can help improve health and public awareness. Aim of the Study This study aims to analyze the causes, health consequences, and available treatment methods for obesity in adults, providing a comprehensive overview of the current knowledge on the subject. Materials and Methods This review utilized data from recent literature published over the last 15 years, sourced primarily from PubMed. The focus was on identifying and synthesizing information related to the epidemiology, risk factors, health consequences, and treatment strategies for adult obesity. Keywords such as "obesity," "adult," "treatment," "epidemiology," and "health consequences" were used to search relevant studies. Conclusions Obesity in adults is a multifaceted issue requiring a comprehensive approach to treatment. Addressing this epidemic necessitates a combination of dietary changes, increased physical activity, behavioral therapies, pharmacological interventions, and surgical options when necessary. Ongoing support and monitoring are essential for achieving long-term success in weight management and improving overall health outcomes.